Science and knowledge in a ludic performance in the spaces of a contemporary city - Kantor, Ryszard (Studia Etnologiczne i Antropologiczne, 2010)
A contemporary consumption society has become the society of fun, which means that fun and entertainment are playing a more and more important role in its culture. A social range and availability of forms of fun broaden. A number of its forms and places of realization grows. Fun is given more and more time, especially in city conglomerations. Among the areas of a socio cultural life one can also find the ones that, as some researchers believe, are strongly placed in the sphere of seriousness. These cover science and knowledge. According to the author, also these spheres of life are not free from the ludic pressure. Innumerable festivals, fairs, science fairs and days, taking place in closed spaces, but also in the open air of a contemporary university city, compete with one another in a ludic presentation of science and knowledge. A symbiosis of fun, science and knowledge seems to be a perfect realization of the idea: to teach entertaining, to entertain teaching. However, it raises certain doubts. The author of the article quotes the warnings, among others, by Neil Postman, who believes that such a light, easy and pleasurable ludic education does not give a reliable and deep knowledge. The education, and knowledge gain should not be an entertainment, but also a hard work. A belief becoming more and more common in the society that everything that is worth familiarising with may or even should take on the form of entertainment, is disastrous and typical of the times when the sphere of seriousness and fun intermingled almost completely.